Aspek-aspek Syariah Dalam Asuransi Syariah - Muhammad Tho’in; Anik Anik (Jurnal Ilmiah Ekonomi Islam, 2015)
This study is to analyze aspects of sharia in Islamic insurance. Theories related to this study include about Ijara, Ijara financing, DSN-MUI fatwa, Ijara financing application. This study is qualitative descriptive. Data collection methods used in this research is the study of literature. The results showed that Takaful insurance aspect is clear then can be applied in the system of Islamic insurance. Takaful is a system where the participants / members / participants donate or donate part or all of the contribution that will be used to pay claims, in case of disaster experienced by most participants/members/participants. The role of the company here is limited to the operational management of insurance companies and investment funds / contributions received or transferred to the company.Keywords: Aspects of Sharia in the Takaful and Insurance Non-Sharia